Performance of Yaskawa Motoman Industrial Robot under Loaded Conditions and Various Distances - Zulkifli, W. Z.; Shamsuddin, S.; Ariston Shah, A. S. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
Introducing robotics into the manufacturing process brings benefits such as an increase in productivity, cost reduction and waste minimization. Robotic equipment is highly accurate with repeatability capability to perform various works. It is important for robot users to know the robot’s current performance compared to its technical specification to ensure its suitability for the current task. Yaskawa Motoman MH5F is an industrial robot commonly used in material handling application. The aim of this project is to investigate the accuracy and repeatability of this robot for different payload and various distances using laser interferometry method. An interferometer is a clear-cut instrument designed to measure objects accurately. Laser interferometry uses the interference method of two or more waves for the purpose of recognizing contrasts between them. There were 12 sets of experiments conducted. For each set of load and distance, the experiment was repeated for 30 times. Results show that the robot repeatability and accuracy value obtained are ±0.0047 mm and ±0.237 mm respectively. Hence, this proved that Yaskawa Motoman MH5F robot has better repeatability compared to the robot’s technical specification, which is ±0.02 mm. Regression analysis carried out using Microsoft Excel displayed the only repeatability against distance factor showing positive linear correlation. For further improvement, this experiment can be carried out with various weight and different distances to identify the machine’s maximum capability.